The Influence of Turbo Marketing and Brand Image on Mixue Ice Cream Purchase Decision In Tasikmalaya - Fauziyah Darwis, Rattu Syahada; Hermawan, Adam; Purwaamijaya, Btari Mariska (Indonesian Journal of Digital Business, 2024)
In the current era of economic recession, Indonesia has even experienced an increase in the economy, quoted to Katadata, one of the main sectors that have become the largest contribution to increasing the economy in Indonesia is the Food and Beverage (FnB) business sector and one of the rapidly growing FnB business sectors is Mixue, which is a Chinese ice cream maker franchise that has entered Indonesia since 2020, Mixue is the largest franchise store in Southeast Asia, However, Mixue has recently been discussed on various social media because it does not yet have halal labeling on its products, but Mixue is quick to respond to the phenomenon that occurs by providing clarification in various media it has, and making digital marketing to maintain the company's brand image to remain good among the public. This study used descriptive quantitative methods, with a total of 110 respondents, the sampling technique used, namely the NonProbability sampling approach with purposive sampling, hypothesis testing was carried out by using SPSS 25 software, As for the hypothetical results of this study, there is a positive and significant influence between turbo marketing variables and purchase decisions, there is a positive and significant influence between brand image variables and purchase decisions, and there is a simultaneous influence between turbo marketing variables and brand image on purchase decisions.